2017
DOI: 10.1186/s41072-017-0019-5
|View full text |Cite
|
Sign up to set email alerts
|

Liner shipping connectivity as determinant of trade

Abstract: Transport connectivity is a crucial determinant of bilateral exports. This paper presents an empirical assessment of the relationship between bilateral maritime liner shipping connectivity and exports in containerizable goods during the period 2006-2013. Making use of probed "gravity" type trade models, the paper incorporates new data on different measurements of maritime distance, as well as a unique new dataset and new bilateral connectivity indices developed by UNCTAD. The empirical investigations unequivoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 102 publications
(94 citation statements)
references
References 20 publications
5
86
0
3
Order By: Relevance
“…Bigger ships and shipping alliances reduce both the number of services (bigger ships) and the number of (independent) competitors on the route (alliances). For more information on UNCTAD's Connectivity Index, see Fugazza and Hoffmann (2017). 18 Similar observations can be made for yard operations, productivity and costs.…”
Section: Figmentioning
confidence: 71%
“…Bigger ships and shipping alliances reduce both the number of services (bigger ships) and the number of (independent) competitors on the route (alliances). For more information on UNCTAD's Connectivity Index, see Fugazza and Hoffmann (2017). 18 Similar observations can be made for yard operations, productivity and costs.…”
Section: Figmentioning
confidence: 71%
“…there exists at least one connection between the ports of two countries), the two countries' GDP values are available, the LSBCI value between the two countries is available, and the two countries' Gb values are positive. ÃÃ [53]. The present study provides insights into understanding such influences at the country level, by focusing on the liner shipping connectivity of individual countries.…”
Section: Discussionmentioning
confidence: 98%
“…Bensassi et al (2015) applied a gravity model to Spanish export data to explain the variability of maritime freight rates and quantify the impact of maritime freight rates on maritime trade. Lastly, Fugazza and Hoffmann (2017) concluded that direct maritime connections, additional transshipment, and container vessel sizes influence bilateral exports, so that "the impact of distance on bilateral exports in classical gravity models is likely to be overestimated".…”
Section: Are Maritime Network Gravitational?mentioning
confidence: 99%